Experimental Study on Fire-Resistance Performance Depending on the Applied Volume of Firestop Material in Metallic and Nonmetallic Penetration Systems - Hong-Beom Choi; A-Yeong Jeong; Jin-O Park; Seung-Yong Hyun; Hyung-Do Lee (Applied Sciences)
This study aims to improve firestop application standards by experimentally analyzing changes in fire-resistance performance due to variations in opening size, penetrant diameter, and firestop material volume. Fire-resistance tests were conducted for 120 min in accordance with KS F ISO 10295-1, using eight specimens with systematically varied cross-sectional areas of openings and penetrants. For nonmetallic pipes, which soften or melt at elevated temperatures, the results show that the completeness of the opening seal and the amount of firestop material are the primary factors governing fire resistance. When the firestop-to-opening area ratio decreased from 95–91%, the maximum temperature on the unexposed surface was, on average, 15–30 °C lower, confirming that modest reductions in firestop material volume for small openings do not compromise performance. In contrast, metallic pipes retained structural integrity and acted as direct heat-transfer paths; fire-resistance performance was more strongly influenced by penetrant diameter and cross-sectional area than by opening size. These findings provide quantitative evidence to support flexible design criteria for firestop systems and offer a practical basis for transitioning toward performance-based approval standards.